TANGGUNG JAWAB NOTARIS PPAT DALAM PELEPASAN HAK ATAS TANAH DENGAN GANTI RUGI YANG MERUGIKAN PIHAK LAIN (Studi Putusan Nomor. 09/Pdt.G/2013/PN.BJ) - Addy Pariudin (Universitas Islam Sumatera Utara, 2018)
The notary has responsibility for the deed he made, if the notary deed causes harm to other parties, then the notary can be held accountable. One of the cases that occurred in the jurisdiction of the Stb District Court, namely a civil lawsuit against the deed of relinquishment of land rights made by a notary who had been examined and put on trial by Binjai District Court with the Verdict Number 09/Pdt.G/2013/PN.Bj. The deed of relinquishment of land rights made by a notary and caused harm to other parties, and then the notary can be held accountable, civilly, administratively and criminally, if the making of the deed is fulfilled with a criminal offense. The legal consequences of relinquishing land rights are detrimental to other parties, namely the cancellation of the deed. As for the conclusion, the authority of a notary in making a deed in the land sector is regulated in Article 15 paragraph (2) letter f of the UUJN, namely making a deed related to land. The notary's responsibility for the deed he made consists of civil, criminal, based on UUJN and based on the code of ethics of the notary profession. In civil law, a person feels that his or her civil rights have been violated, then that person has the right to file a claim for compensation and the acquisition of the violated rights. The Verdict No. 09/Pdt.G./2013/PN Bj, it appears that the role of a notary in this case is to make a deed of relinquishment of rights between Defendant II to Defendant XVII to Defendant I. Meanwhile, the notary must know or must first know the validity of the deed. The land deed is related to the legal action desired by the appearers, by checking with the National Land Agency. Keywords: Liability, Notary, Release of Land Rights.